Chronic rhinosinusitis with nasal polyps: predictive factors for recurrence and revision surgery - Salvador, Pedro; Lombo, Catarina; Silva, Francisco Moreira da; Fonseca, Rui (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) is an inflammatory condition which may have a significant impact on quality of life. Endoscopic sinus surgery (ESS) is indicated for patients refractory to maximal medical treatment and presents high recurrence and revision surgery rates. Aim of the study was to evaluate ESS outcome in CRSwNP management and to assess independent predictive factors for recurrence and revision surgery. Methods: Retrospective medical chart review of patients who underwent ESS for recalcitrant CRSwNP, from January 2013 to December 2017, with a minimum follow-up time of 12 months. Results: This study enrolled 132 patients, 62.1% of whom were males, with a mean age of 43.4±11.5 years. Asthma was the most common comorbidity (39.4%, n=52) and aspirin exacerbated respiratory disease (AERD) was present in 9.8% (n=12) of the study population. We found a recurrence rate of 34.1% (n=45) and 9% (n=12) of patients required revision surgery. Multivariate analysis identified as independent variables of recurrence (95% CI): a history of asthma (OR=8.81, CI 3.87-20.03; p<0.001) and a severe Lund-Mackay score (17-24) (OR=5.85, CI 2.73-12.51; p=0.001). Revision surgery was related to a severe endoscopic Lund-Kennedy score at presentation (OR=4.05, CI 1.91-8.01, p=0.001). Conclusions: CRSwNP presents a high tendency to recur after ESS. Asthma, severe sinus opacification and severe endoscopic score are poor prognostic factors that hallmark a more aggressive disease. A more extensive surgical procedure and/or middle turbinate resection with a rigorous postoperative compliance should be considered to improve long term results.